Time-varying characteristics of the simultaneous interactions between economic uncertainty, international oil prices and GDP: A novel approach for Germany - Tunç, Ahmet; Koçoğlu, Mustafa; Aslan, Alper (ELSEVIER SCI LTD, 2022)
This study is the first attempt to analyze the simultaneous time-varying interactions among international oil prices, economic policy uncertainty (EPU) and output for the German economy. Contrary to similar results in the literature, this study reports strikingly interesting findings. First, the responses of the German GDP to both uncertainty and international oil price shocks are time-varying, and these responses are significantly affected by the major historical events such as the Global Financial Crisis and the oil price collapse of 2014. Second, oil price shocks trigger negative responses of EPU, but these responses turn to positive in periods such as the Iraq invasion, the GFC of 2008–2009, and the oil price collapse of 2014. Third, while the responses of the German GDP to EPU shocks are affected by the prevailing economic and political conditions, the responses of EPU to GDP shocks are consistently negative. Finally, the overall responses of international oil prices to the German EPU shocks are negative in the short-term, while these responses in the medium- and long-term are insignificant.
Keywords: Economic policy uncertainty; International oil prices; Time-varying parameter vector autoregression; Germany